Atherosclerosis : risks, mechanisms, therapies - Wang, Hong, 1956 September 19-; Patterson, Cam (Hoboken, New Jersey : Wiley Blackwell, 2014)
Comprehensive and in-depth in its coverage, Atherosclerosis: Cellular, Molecular & Biochemical Mechanism and Novel Therapy reviews the recent progress in atherosclerosis research and offers cutting edge perspectives from experts in the field. Written by an international team of authors including leading physician-scientists, research experts and physicians, chapters are divided into four major sections, covering risk factors, cellular and molecular mechanisms, biochemical mechanisms and novel and future therapeutics. Atherosclerosis: Cellular, Molecular & Biochemical Mechanism and Novel The.
Lifestyle Factors and Cardiovascular Disease in the YoungPhysical Activity; Diet and Nutrition; Environmental Effects; Ambient Air Pollution; Other Environmental Factors; Summary; References; Section II Cellular Mechanisms; Chapter 9 Endothelial Cells; Introduction; Endothelial Nitric Oxide; Flow and Arterial Shear Stress; Peroxisome Proliferator-Activated Receptor Nuclear Receptor Family; Endothelial Progenitor Cells; Future Directions; References; Chapter 10 Vascular Smooth Muscle Cells; Introduction; SMCS in Atheroma Progression; Extrinsic Control of SMC Biology.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Atherosclerosis; Atherosclerosis -- Pathophysiology; Atherosclerosis -- Prevention; Atherosclerosis -- Treatment; Coronary Artery Disease -- physiopathology; Coronary Artery Disease -- prevention & control; Coronary Artery Disease -- therapy; Atherosclerosis; Cerebrovascular disease; Medicine; MEDICAL -- Surgery -- General; Atherosclerosis; Atherosclerosis -- Pathophysiology; Atherosclerosis -- Prevention; Atherosclerosis -- Treatment; Electronic books